2009
DOI: 10.1038/pcan.2009.12
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and metabolic complications during androgen deprivation: exercise as a potential countermeasure

Abstract: Apart from the well-established adverse musculoskeletal and sexual health effects of androgen deprivation therapy (ADT), evidence is accumulating of substantial ADT-related cardiovascular and metabolic complications, which may impact quality of life and overall survival. In this brief review we discuss (1) the incidence of cardiovascular and metabolic complications during/ following ADT from large cohort studies, (2) the increased risk factors for cardiovascular and metabolic disease from cross-sectional and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 74 publications
(105 reference statements)
2
27
0
Order By: Relevance
“…On the one side, leg press performance was untypically low in the study by Winters-Stone et al (2016) [38]. On the other side, the respective results were untypically high and unsteady in the trial by Galvao et al (2006) [27] (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the one side, leg press performance was untypically low in the study by Winters-Stone et al (2016) [38]. On the other side, the respective results were untypically high and unsteady in the trial by Galvao et al (2006) [27] (Fig. 3).…”
Section: Discussionmentioning
confidence: 96%
“…However, it might be limited regarding the development of sheer leg strength, especially when the participants are elderly PCaPs receiving cancer treatment and when strength outcome is measured with a standard 1RM test on the leg press. Galvao et al (2006) [27], on the other hand, who reported very high outcomes, did not only assess 1RM but also measured muscle endurance. Their participants performed the maximal number of repetitions at 70% of their 1RM and, in contrast to the participants of the other studies, might therefore have had a learning effect when performing at complete exhaustion, which might be a decisive factor for 1RM performance [81].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supervised group sessions have been shown to provide a socially stimulating and motivating environment that is more conducive to adherence and retention than home‐based exercises alone . This is concordant with our own findings, with the majority of participants in the group sessions reporting them to be motivating, and continuing to exercise 6 months after commencing the programme.…”
Section: Discussionmentioning
confidence: 99%
“…The well-known side effects of CAS like sexual dysfunction, hot flushes, fatigue, cardiovascular complications, osteoporosis, weight gain and anemia have significant implications for quality of life (Malone, et al, 2005;Freedland, et al, 2009;Galvão, et al 2009). Since androgens are essential for the regulation of fat distribution, insulin sensitivity and lipid and bone metabolism, recent publications focussed on the concept that CAS may also be associated with an increase in overall and in particular cardiovascular morbidity and mortality (Corona, et al, 2011).…”
Section: Side Effects Of Androgen Suppression Therapymentioning
confidence: 99%